The Evaluation of Regional Spatial Plan for 2011-2031 Based on Land Use Changes Prediction Using Cellular Automata-Markov Model in Sleman - Linggar Esty Hardini; Ana Noveria (Amcolabora, 2021)
In the past years, the development of Sleman Regency has been considered rapid as evidenced by the emergence of built up areas including expansion of the university areas, shopping malls, and housing. Along with the increase in the total population, university students and workers from other regions coming to this regency, the land use in Sleman Regency has started to shift. Land use changes need to be controlled by predicting land use using the CA-Markov model. CA-Markov modeling has dynamic properties that integrate the dimensions of space and time, where the occurrence of events is determined by events that directly precede them and can be used to predict the next event. The accuracy of the CA-Markov concept can be determined by validation and expressed in the Kappa coefficient value (≥ 0.70). This CA-Markov concept has been developed since the 1940s in the field of computers by Von Neumann and Ulam. In this concept it is assumed that pixels are the beginning of the mathematical concept. When a pixel changes, its new status is only affected by its old status and the neighbor status. This research was conducted to predict the land use in 2031 using the Cellular Automata-Makov model, evaluate the use of land in 2031 in relation to RTRW or city plan, and create a scenario of the direction for land use control in 2031 for disaster-prone areas. Based on the prediction of land use in Sleman Regency in 2031, Kappa coefficient was obtained at 0.7399, implying that the suitability of spatial area and distribution reached 73.99% which is considered good. The results of the prediction also showed that in 2031, the land use would be dominated by building area which was predicted to reach 43.53% out of the total area. The evaluation of land use prediction in 2031 based on RTRW method showed that as large as 40.137,39 ha land would be used according to the RTRW, while 17.411,00 ha would not be used accordingly. The improper use of land might be due to the shift in the use of 4.659,18 ha of rice fields into buildings.